Optimizing Voriconazole Susceptibility Testing of Candida: Effects of Incubation Time, Endpoint Rule, Species of Candida, and Level of Fluconazole Susceptibility - Lozano-Chiu, M. (American Society for Microbiology, 1999)
Voriconazole is a new triazole antifungal agent that has potent activity against many isolates of Candida, including Candida krusei and Candida glabrata. In this work, we studied the impact of glucose supplementation, incubation time, agitation of the plates prior to reading, endpoint determination rule, visual versus spectrophotometric reading, Candida species, and fluconazole MIC on the MIC of voriconazole for Candida isolates tested by using the microdilution format assay of the National Committee for Clinical Laboratory Standards (NCCLS) M27-A antifungal susceptibility testing methodology. For both voriconazole and fluconazole, a spectrophotometric endpoint of 50% reduction in turbidity relative to the growth control correlated most closely with the NCCLS-defined visual endpoint of “prominent decrease in turbidity.” Correlation was generally better after 24 h of incubation than after 48 h. Supplementation of the medium to contain 20 g of glucose/liter did not alter the MIC significantly but did enhance growth and simplify visual readings. All Candida species appeared potentially susceptible to voriconazole, including isolates of C. krusei. For some isolates for which fluconazole MICs were markedly elevated voriconazole MICs were also elevated, but the clinical significance of these observations remains to be determined.